Twitchin as a regulator of catch contraction in molluscan smooth muscle - FUNABARA, DAISUKE (2005)
Molluscan catch muscle can maintain tension for a long time with little energy consumption. This unique phenomenon is regulated by phosphorylation and dephosphorylation of twitchin, a member of the titin/connectin family. The catch state is induced by a decrease of intracellular Ca(2+) after the active contraction and is terminated by the phosphorylation of twitchin by the cAMP-dependent protein kinase (PKA). Twitchin, from the well-known catch muscle, the anterior byssus retractor muscle (ABRM) of the mollusc Mytilus, incorporates three phosphates into two major sites D1 and D2, and some minor sites. Dephosphorylation is required for re-entering the catch state. Myosin, actin and twitchin are essential players in the mechanism responsible for catch during which force is maintained while myosin cross-bridge cycling is very slow. Dephosphorylation of twitchin allows it to bind to Factin, whereas phosphorylation decreases the affinity of the two proteins. Twitchin has been also been shown to be a thick filament-binding protein. These findings raise the possibility that twitchin regulates the myosin cross-bridge cycle and force output by interacting with both actin and myosin resulting in a structure that connects thick and thin filaments in a phosphorylation-dependent manner.